2022
DOI: 10.3389/fphar.2022.956788
|View full text |Cite
|
Sign up to set email alerts
|

The influence of baseline characteristics on the efficacy of immune checkpoint inhibitors for advanced lung cancer: A systematic review and meta-analysis

Abstract: Purpose: To investigate the impact of different baseline characteristics on the efficacy of immune checkpoint inhibitors (ICIs) for advanced lung cancer.Methods: In order to identify eligible randomized controlled trials (RCTs), a systematic search was conducted in PubMed, Embase, Web of Science, and Scopus Cochrane Library databases. The primary outcomes were hazard ratios (HRs) and 95% confidence intervals (CIs) for overall survival (OS). To explore the potential interaction during the administration of ICI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…As demonstrated in other cohort studies and RCTs, the presence of liver metastases was negatively associated with DCB and OS [ 44 , 45 , 46 ]. A study of patients with malignant melanoma showed that liver metastases had significantly lower T-cell infiltration and increased TIM-3 expression than lung and lymph node metastases [ 47 ].…”
Section: Discussionsupporting
confidence: 60%
“…As demonstrated in other cohort studies and RCTs, the presence of liver metastases was negatively associated with DCB and OS [ 44 , 45 , 46 ]. A study of patients with malignant melanoma showed that liver metastases had significantly lower T-cell infiltration and increased TIM-3 expression than lung and lymph node metastases [ 47 ].…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies on the impact of smoking on OS of immunotherapy have produced conflicting results. 55,56 A meta-analysis by Xiao et al 56 suggested that non-smokers with advanced lung cancer benefit more from ICIs combination therapy, while smokers benefit more from ICIs monotherapy. Notably, our statistical analysis did not find significant differences in the incidence of irAEs between stroma-L and stroma-H groups, suggesting that iTSP does not impact the safety of ICIs treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that past or current smoking was independently associated with worse survival compared to never smoking. Previous studies on the impact of smoking on OS of immunotherapy have produced conflicting results 55,56 . A meta‐analysis by Xiao et al 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall effectiveness and safety of immunotherapy utilizing ICIs have been generally demonstrated in patients afflicted with metastatic and locally advanced non-small cell lung cancer (NSCLC) (8), as well as small cell lung cancer (SCLC) (9). However, subsequent observations suggest that the therapeutic response to ICIs may vary in individual patients with lung cancer (10). Accordingly, uncovering of the clinical factors that are related to the efficacy of ICIs in patients with lung cancer is of great clinical significance.…”
Section: Introductionmentioning
confidence: 99%